2008
DOI: 10.1093/humrep/den048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed markers in human follicular cells associated with competent oocytes

Abstract: Microarray technologies are useful to mine the transcriptome of FCs expressed in follicles associated with competent oocytes and could be used to improve embryo selection with the objective of successful single embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
149
2
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(166 citation statements)
references
References 62 publications
3
149
2
12
Order By: Relevance
“…that there is a positive correlation between CC gene expression and oocyte quality. Moreover, there are large variations in the number of "sensible" specific gene markers for ongoing pregnancy, from four [21] to 630, and then 45 for the same group, the majority being up-regulated [18,19]. It is not clear that a high level of expression in CC at this stage is a sign of quality: the cumulus cells have reached the end of their life's journey, especially after cumulus expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that there is a positive correlation between CC gene expression and oocyte quality. Moreover, there are large variations in the number of "sensible" specific gene markers for ongoing pregnancy, from four [21] to 630, and then 45 for the same group, the majority being up-regulated [18,19]. It is not clear that a high level of expression in CC at this stage is a sign of quality: the cumulus cells have reached the end of their life's journey, especially after cumulus expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on clinical data has been recorded. Cumulus cell transcript analyses were studied, as they are thought to represent a non-invasive approach for assessment of oocyte quality and molecular events triggered by FSH-based stimulation protocols [18][19][20][21]. Microarray technology offers a throughput transcript analysis tool to evaluate the effect of different FSH isoform mixes on biological and molecular pathways during ovarian stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, quantitative real-time RT-PCR analysis of genes from human cumulus cells was predictive of the quality of their enclosed oocytes [12,29,46]. These observations were further supported by subsequent studies that measured global gene expression of cumulus cells, which was concluded to be a non-invasive test for oocyte/embryo quality [2,3,15,41]. Granulosa and cumulus cell gene expression profiling has also been used to compare the effects of recombinant FSH vs. human menopausal gonadotrophin (hMG) [6,14], floating vs. cumulus granulosa cells [22], cumulus cells from lean vs. overweight-obese PCOS patients [21], and ovarian reserve status in young women with diminished ovarian reserve [39].…”
Section: Introductionmentioning
confidence: 69%
“…For example, large-scale microarray analyses have identified a correlations between ferridoxin (FDX1), aromatase (CYP19A1), and CDC42 levels in follicular cells and oocyte competence [51], and between BCL2L11, PCK1 and NFIB levels in cumulus cells and embryo potential and the likelihood of a successful pregnancy [52]. However, large scale microarray studies are currently not feasible for oocyte quality assessment.…”
Section: Discussionmentioning
confidence: 99%